Drug Delivery Strategies for Curcumin and Other Natural Nrf2 Modulators of Oxidative Stress-Related Diseases - Nina Katarina Grilc; Matej Sova; Julijana Kristl (MDPI AG, 2021)
Oxidative stress is associated with a wide range of diseases characterised by oxidant-mediated disturbances of various signalling pathways and cellular damage. The only effective strategy for the prevention of cellular damage is to limit the production of oxidants and support their efficient removal. The implication of the nuclear factor erythroid 2-related factor 2 (Nrf2) pathway in the cellular redox status has spurred new interest in the use of its natural modulators (e.g., curcumin, resveratrol). Unfortunately, most natural Nrf2 modulators are poorly soluble and show extensive pre-systemic metabolism, low oral bioavailability, and rapid elimination, which necessitates formulation strategies to circumvent these limitations. This paper provides a brief introduction on the cellular and molecular mechanisms involved in Nrf2 modulation and an overview of commonly studied formulations for the improvement of oral bioavailability and in vivo pharmacokinetics of Nrf2 modulators. Some formulations that have also been studied in vivo are discussed, including solid dispersions, self-microemulsifying drug delivery systems, and nanotechnology approaches, such as polymeric and solid lipid nanoparticles, nanocrystals, and micelles. Lastly, brief considerations of nano drug delivery systems for the delivery of Nrf2 modulators to the brain, are provided. The literature reviewed shows that the formulations discussed can provide various improvements to the bioavailability and pharmacokinetics of natural Nrf2 modulators. This has been demonstrated in animal models and clinical studies, thereby increasing the potential for the translation of natural Nrf2 modulators into clinical practice.